Dissemination of a Controversial COVID-19 ‘Miracle Cure’ on Twitter: The Case of Chlorine Dioxide - Sauvayre, Romy (New Ideas Concerning Arts and Social Studies Vol. 3, 2025)
The COVID-19 pandemic has given rise to all types of beliefs, theories, and explanations, whether scientific, religious, or conspiratorial. At the beginning of the pandemic, science did not yet have a medicinal product for this new disease, and alternative medicines offering “miracle cures” were acclaimed by some citizens looking for an effective treatment for COVID-19. The content of these beliefs then evolves with our societies to include additional current aspects, such as distrust of authorities, conspiracy theories, or antivaccinism. Adherence to conspiratorial beliefs, alternative medicine, and rejection of political or medical authorities have affected the way citizens accept recommendations concerning COVID-19. This study aims to study a specific “miracle cure”, namely, chlorine dioxide, a bleaching agent for textiles or paper that also has disinfectant properties (water, surfaces). The dissemination of information about chlorine dioxide to French-speaking people on the social network Twitter from 1 December 2019 to 30 November 2021 is analysed using a graph network. A total of 1,252 messages were collected, containing 596 unique tweets. An analysis of tweets per user was conducted to identify bot accounts, and fake users were removed from the collected data. The results show that messages promoting misinformation, even if they are likely to be quantitatively less numerous, spread more widely than those based on more reliable information. In addition, this article shows that chlorine dioxide was promoted as an effective cure by medical doctors and peer-reviewed articles, which consequently increased the dissemination of this belief in the social space. Consequently, the process of misinformation entered the sphere of scientific controversy. When scientists have unverified beliefs and try to publish them, the beliefs become potential knowledge until the process of replication allows the scientific community to decide. The boundary between science and misinformation is becoming blurred to the point that it is no longer possible until proven otherwise to call chlorine dioxide a “false miracle cure” but a controversial treatment against COVID-19.